CHARACTERIZATION OF MAGNETIC AND GEOCHEMICAL PROPERTIES OF VOLCANIC AND NON-VOLCANIC IRON SAND IN INDONESIA - Miranda, Rizka
Iron sand can be distinguished into volcanic iron sand and non-volcanic iron sand depending on the source of iron sand. Volcanic iron sand and non-volcanic iron sand can be identified based on the characteristics of both the magnetic and mineral contained, where later each iron sand can be used for industrial products of high value. Therefore, this study aims are to determine the differences in the characteristics of two different types of volcanic and non-volcanic iron sand based on the grain size of the sand, susceptibility value, and the content of elements and minerals. The samples used in this study were the iron sand of Bayuran Beach as volcanic ironsand and the downstream Tor River as nonvolcanic iron sand. The methods used in this study were a combination of magnetic method and geochemical methods. The magnetic method used in this study was the analysis of susceptibility values, while the geochemical methods were X-Ray Flourence (XRF), X-Ray Diffraction (XRD), and Rare Earth Element (REE) analysis. Based on the results, Bayuran beach iron sand is dominated by fine sand size with susceptibility values between 1129,1x10-8 m3/kg to 4131,7x10-8 m 3/kg. Bayuran beach iron sand is dominated by titanomagnetite minerals with high REE. Whereas downstream Tor River iron sand is dominated by mediumsized sand with a susceptibility value between 461x10-8 m3/kg to 16857.3x10-8 m 3/kg. The iron sand of the downstream Tor River contains augite and nontronite minerals and dominated by Sc. Based on these results, the volcanic dan nonvolcanic iron sand have different characteristic.